Pengaruh Penunasan dan Pemberian Pupuk NPK Phonska Terhadap Produksi Tanaman Kelapa Sawit (Elaeis guineensis jacq) - Haminin Haminin; Tutik Nugrahini; Purwati Purwati (Agrifarm : Jurnal Ilmu Pertanian, 2012)
Penunasan influence and NPK fertilizer production plant Phonska against oil palm (Elaeis guineensis jacq). The aim of research to determine the effect penunasan, Phoska NPK fertilizer and its interaction with the production of oil palm plantations. Research carried out for 4 months, starting from May to August 2010. The location of the research in the Garden State Agricultural Polytechnic Pilot Samarinda. Research arranged in a randomized block design (RAK) with 2 x 4 factorial experiment 3 times the number of replicates. The treatment consists of two factors: The first factor is Penunasan (P) which comprises, namely: p0 = without penunasan, p1 = with penunasan. The second factor is Phonska NPK fertilizer which consist of 4 levels, namely: m0 = 0 kg / plant, m1 = 0.5 kg / staple crops, m2 = 1.0 kg / plant, m3 = 1.5 kg / plant. The results showed the treatment penunasan very significant effect on the weight and number of TBS TBS. Penunasan best treatment on p1 (with penunasan). , NPK fertilizer treatment Phonska very significant effect on the increase in production of oil palm plantations. There is interaction between treatment penunasan with NPK fertilizer production peningkataan Phonska against oil palm plantations.